Aggregation Function Constructed from Semi-copula - Boonyasri, Varayut; Tasena, Santi (Thai Journal of Mathematics, 2023)
In this work, we show that almost all aggregation functions can be constructed by composing semi-copulas and tuples of non-decreasing univariate functions. In particular, this construction method works for all strictly increasing aggregation functions. This method also resembles Sklar's construction of multivariate distribution functions. As a demonstration, construction examples via this method are also given.